Screening the Stage : Case Studies of Film Adaptations of Stage Plays and Musicals in the Classical Hollywood Era, 1914-1956 - Neale, Stephen, 1950- (Project Muse, 2017)
Introduced by a comprehensive account of the factors governing the adaptation of stage plays and musicals in Hollywood from the early 1910s to the mid-to-late 1950s, Screening the Stage consists of a series of chapter-length studies of feature-length films, the plays and musicals on which they were based, and their remakes where pertinent. Founded on an awareness of evolving technologies and industrial practices rather than the tenets of adaptation theory, particular attention is paid to the evolving practices of Hollywood as well as to the purport and structure of the plays and stage musicals on which the film versions were based. Each play or musical is contextualized and summarized in detail, and each film is analyzed so as to pinpoint the ways in which they articulate, modify, or rework the former. Examples range from dramas, comedies, melodramas, musicals, operettas, thrillers, westerns and war film, and include The Squaw Man, The Poor Little Rich Girl, The Merry Widow, 7th Heaven, The Cocoanuts, Waterloo Bridge, Stage Door, I Remember Mama, The Pirate, Dial M for Murder and Attack.